THE INTEGRATION OF FOOD HERITAGE WITH SUSTAINABLE DEVELOPMENT GOALS - Sabanmanee, Natthaporn; Sarasuk, Chanon; Sukkaseam, Kritchanok; Maneenin, Wassakorn (Academic Journal Phranakhon Rajabhat University, 2025)
This article discusses integrating food heritage with the Sustainable Development Goals (SDGs). To promote sustainable development, preserve cultural identity, and support local economies. It also, addressed the global challenges such as poverty reduction, environmental conservation, and social inclusion when integrating food heritage with SDGs. A food heritage is the cultural, social, and historical influence conveyed by food, and it is important to personal and community identities. It is the traditional knowledge and skill about agriculture, culinary, and biodiversity that is supported in a territory. It is noteworthy that recognition and valorization of food heritage could contribute to food security, improve livelihoods, reduce, and preserve local culture and sustainable traditional ways of food for future generations. Embedding food heritage into the SDGs therefore provides an opportunity to solve global challenges, ranging from poverty eradication to environmental conservation and social inclusion. Long-term socioeconomic opportunities include promoting indigenous crops, culinary practices, and cultural tourism for marginalized communities. Preserving food heritage supports economic development, tourism, cultural identity, and biodiversity conservation. Embracing sustainable agricultural practices with indigenous crops enhances ecosystem health and environmental sustainability. Traditional diets, rich in nutrients and healthy preparation methods, also help prevent diet-related diseases